Edukasi Ortotik-Prostetik untuk Meningkatkan Literasi Kesehatan dan Pengenalan Karier pada Siswa Sekolah Menengah - Nuzfi Harvandi, Annisa; Mandasari Ningsih, Cica Tri; Fatati, Muhibbah (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Prosthetic Orthotic Education is the study that engaged in health services in the manufacture of artificial limbs (prosthetic) and supportive limb device (orthosis), while the Prosthetic Orthotic Profession is a health worker who works in the field of prosthetic orthotics. In Indonesia, many people do not know about Prosthetic Orthotic Education and the Prosthetic Orthotic Profession. So that it offers education to high school students who are considered effective to increase their knowledge. The study was conducted in April 2022. The purpose of this study was to determine the effect of education on Prosthetic Orthotic Education and Prosthetic Orthotic Profession on the knowledge of 11th grade high school students at SMAN 1 Ngemplak. Methods: This community service activity aimed to improve to examine the impact of orthotics and prosthetics education, on the knowledge and awareness of 11th-grade students at SMAN 1 Ngemplak. The activity involved 40 students and was carried out through material presentations, interactive discussions, and question and answer sessions that emphasized basic concepts, tool functions, and the role of professionals in rehabilitation. Results: The results showed a significant shift in knowledge: the proportion of students in the Good category increased from 35% (14/40) to 95% (38/40), while the Fair category decreased from 60% to 5% and the Poor category from 5% to 0%. The activity ran smoothly with active student participation and school support. Conclusion: Orthotic-prosthetic education at the secondary school level is effective in improving health literacy and career understanding; follow-up in the form of simple practical sessions or educational visits is recommended to deepen understanding.